2017
DOI: 10.1016/j.idm.2016.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Role of short-term dispersal on the dynamics of Zika virus in an extreme idealized environment

Abstract: In November 2015, El Salvador reported their first case of Zika virus (ZIKV) infection, an event followed by an explosive outbreak that generated over 6000 suspected cases in a period of two months. National agencies began implementing control measures that included vector control and recommending an increased use of repellents. Further, in response to the alarming and growing number of microcephaly cases in Brazil, the importance of avoiding pregnancies for two years was stressed. In this paper, we explore th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 41 publications
0
25
0
Order By: Relevance
“…An approximation of the basic reproductive number was obtained using maximum likelihood methods. Finally, a study of the impact of short term dispersal on the dynamics of Zika virus is analyzed in [27]. The model formulated within [27] does distinguish between asymptomatic and symptomatic infected populations, and focuses on the estimation of the reproductive number between two close communities.…”
Section: Introductionmentioning
confidence: 99%
“…An approximation of the basic reproductive number was obtained using maximum likelihood methods. Finally, a study of the impact of short term dispersal on the dynamics of Zika virus is analyzed in [27]. The model formulated within [27] does distinguish between asymptomatic and symptomatic infected populations, and focuses on the estimation of the reproductive number between two close communities.…”
Section: Introductionmentioning
confidence: 99%
“…In their work, they considered only treatment as a control measure in a single infectious compartment to model the trans-mission dynamics. A similar work can be traced to [10] who extended the work by [6]. In their extension, [10] treated Zika virus infection to be a vector-borne infection alone, and considered infection with Zika virus to be either symptomtic or asymptomatic and divided the infectious compartment accordingly.…”
Section: Introductionmentioning
confidence: 99%
“…A similar work can be traced to [10] who extended the work by [6]. In their extension, [10] treated Zika virus infection to be a vector-borne infection alone, and considered infection with Zika virus to be either symptomtic or asymptomatic and divided the infectious compartment accordingly. A similar mathematical model for the dynamics of Zika virus in the presence of a vector was developed by [11].…”
Section: Introductionmentioning
confidence: 99%
“…e authors in [27] investigated the dynamics of Ebola virus with time delay and fractional order and reported that combination of time delay and fractional order can effectively enrich the dynamics and strengthen the stability condition of the infection model. Analysis and dynamics of Zika transmission have been examined by many researchers (see, e.g., [3,28,29]. In [3], a mathematical model for transmission of Zika virus has been proposed with control measures of Zika virus.…”
Section: Introductionmentioning
confidence: 99%